THE CRUCIAL ROLE OF RESEARCH MIDWIVES: SIGNIFICANCE AND IMPLEMENTATION - Syed Suheel Ahmad Baba (PT. Radja Intercontinental Publishing, 2023)
In the pursuit of providing women with the most current evidence-based care, high-quality research becomes paramount. Midwives, being uniquely positioned to understand the needs of pregnant women, can play a vital role in multidisciplinary research teams. They possess a range of skills essential for research, making them invaluable contributors. The role of a research midwife encompasses diverse responsibilities such as study design, participant recruitment and consent, data collection and analysis, as well as result dissemination. Engaging in this role not only allows midwives to refine existing skills but also presents ample opportunities for acquiring new ones. The experience gained as research midwives can pave the way for a gratifying career in research or significantly enhance their clinical practice.